A bio-based route to the carbon-5 chemical glutaric acid and to bionylon-6, 5 using metabolically engineered Corynebacterium glutamicum. Issue 20 (24th September 2018) - Rohles, Christina Maria; Gläser, Lars; Kohlstedt, Michael; Gießelmann, Gideon; Pearson, Samuel; del Campo, Aránzazu; Becker, Judith; Wittmann, Christoph
Abstract : Here, we present a green route to glutaric acid, a chemical of recognized industrial value, using a tailor-made cell factory. Abstract : In the present work, we established the bio-based production of glutarate, a carbon-5 dicarboxylic acid with recognized value for commercial plastics and other applications, using metabolically engineered Corynebacterium glutamicum . The mutant C. glutamicum AVA-2 served as a starting point for strain development, because it secreted small amounts of glutarate as a consequence of its engineered 5-aminovalerate pathway. Starting from AVA-2, we overexpressed 5-aminovalerate transaminase ( gabT ) and glutarate semialdehyde dehydrogenase ( gabD ) under the control of the constitutive tuf promoter to convert 5-aminovalerate further to glutarate. The created strain GTA-1 formed glutarate as a major product, but still secreted 5-aminovalerate as well. This bottleneck was tackled at the level of 5-aminovalerate re-import. The advanced strain GTA-4 overexpressed the newly discovered 5-aminovalerate importer NCgl0464 and formed glutarate from glucose in a yield of 0.27 mol mol −1 . In a fed-batch process, GTA-4 produced more than 90 g L −1 glutarate from glucose and molasses based sugars in a yield of up to 0.70 mol mol −1 and a maximum productivity of 1.8 g L −1 h −1, while 5-aminovalerate was no longer secreted. The bio-based glutaric acid was purified to >99.9% purity. Interfacial polymerization and melt polymerization with hexamethylenediamine yielded bionylon-6, 5, a polyamide with a unique structure.